Tracing metabolite profiles in human milk: Studies on the odorant 1,8-cineole transferred into breast milk after oral intake. - Kirsch, Frauke; Horst, Kathie; Röhrig, Waldemar; Rychlik, Michael; Büttner, Andrea (Metabolomics, 2013)
The transfer of certain substances from the maternal diet or medication into breast milk has been known for many years. There is currently also an increasing interest in odorants in human milk and their potential influence on the breastfed child. Nevertheless, metabolic products originating from bioconversion of odorants within the maternal organism have hitherto not been considered. Breastfed children may take in xenobiotic compounds that are transferred unmodified into human milk, but also their metabolic derivatives. Metabolic activation is a crucial point for evaluation of both positive and negative biological effects, thus it is important to understand the basic principles of metabolism in human milk. The present study investigated metabolite profiles of the odorant 1,8-cineole (eucalyptol) in human milk after lactating mothers ingested a non-prescription pharmaceutical (Soledum®) containing this substance. Ten different metabolites were identified, five of which have been previously described in humans and other mammals (α2-hydroxy-1,8-cineole, β2-hydroxy-1,8-cineole, α3-hydroxy-1,8-cineole, 7-hydroxy-1,8-cineole, 9-hydroxy-1,8-cineole). Three of the metabolites have hitherto only been found in microorganisms and insects (2-oxo-1,8-cineole, 3-oxo-1,8-cineole, 2,3-dehydro-1,8-cineole) and the derivatives α2,3-epoxy-1,8-cineole and 4-hydroxy-1,8-cineole have never before been identified as metabolites of 1,8-cineole. Metabolism profiles showed large inter- and intra-individual differences and were strongly related to sampling time. Identification and relative quantification of the metabolites were accomplished by gas chromatography–mass spectrometry (GC–MS) after preparation of the human milk extracts by solvent assisted flavour evaporation (SAFE). Synthesised reference substances were used to confirm the chemical identity of the detected substances.<br